Temperature dependent Raman spectroscopy of chemically derived few layer MoS2 and WS2 nanosheets - Thripuranthaka, M.; Kashid, Ranjit V.; Rout, Chandra Sekhar; Late, Dattatray J. (Applied Physics Letters, 2014)
We have systematically investigated the temperature dependent Raman spectroscopy behavior of a few layered MoS2 and WS2 nanosheets synthesized using simple hydrothermal method. Our result reveals A(1g) and E-2g(1) modes soften as temperature increases from 77 K to 623 K. This behavior can be explained in terms of a double resonance process which is active in single-and few layer thick nanosheets. The frequency shifts and peak broadening can provide unambiguous, nondestructive, and accurate information of a few layered MoS2 and WS2. This mechanism can also be applicable in characterizing the structural, optical, electronic, and vibrational properties of other emerging layered materials. (c) 2014 AIP Publishing LLC.